78.0k views
2 votes
30 POINTS! Solve the following equation for l. A = 2πr + πrl. Explain each step.

User Deion
by
4.6k points

2 Answers

2 votes

Answer:

l =
(A-2\pi r)/(\pi r)

Explanation:

Given

A = 2πr + πrl ( isolate the term in l by subtracting 2πr from both sides )

A - 2πr = πrl ( divide both sides by πr )


(A-2\pi r)/(\pi r) = l

User Pankaj Tiwari
by
5.2k points
5 votes

Answer: l = A/πr - 2

Explanation:

The given equation is

A = 2πr + πrl

The first step is to subtract 2πr from the left hand side and the right hand side of the equation. It becomes

A - 2πr = 2πr + πrl - 2πr

A - 2πr = πrl

The next step is to divide the left hand side and the right hand side of the equation by πr. It becomes

(A - 2πr)/πr = πrl/πr

l = (A - 2πr)/πr

I = A/πr - 2πr/πr

I = A/πr - 2

User Noel Baron
by
5.2k points